The rhesus monkey as an animal model for training in interventional neuroradiology. - terBrugge, K; Lasjaunias, P; Chiu, M C; Marotta, T R; Tatton, W; Glen, J (American Journal of Neuroradiology, 1989)
The angiographic anatomy of the external carotid artery system in the rhesus monkey is described. Similarities and differences between human and monkey anatomy are emphasized, as well as anatomic variations and potential collateral pathways. Superselective angiography and embolization in the external carotid artery system of the rhesus monkey proved to be technically feasible and potentially represents an excellent training model for surgical neuroangiographic techniques.